1997
DOI: 10.2136/sssaj1997.03615995006100010006x
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis for Determination of Dye Tracer Concentrations in Sand Columns

Abstract: Dye tracers can be used to visualize flow paths in soils. We used digital image analysis to determine the spatial distribution of dye concentrations in a quartz sand column. Color slides and near‐infrared black‐and‐white photographs were taken from a sand column that was cut in halves longitudinally after a point‐source dye infiltration experiment. In a separate calibration experiment, sand samples were prepared with known water content and dye concentration. Photographs of such sample arrays were used as trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Using the dye coverage and the relative bromide concentration we can calculate a retardation factor for the dye. The lowest detectable dye concentrations encountered in some studies are 0.1 g l 21 (Ewing and Horton, 1999) and 0.2 g l 21 (Aeby et al, 1997). Forrer et al (2000) reported a lower limit of 0.04 g l 21 soil, however, they did not report the water content.…”
Section: Comparison Of Bromide and Dye Coverage In One Fingermentioning
confidence: 88%
“…Using the dye coverage and the relative bromide concentration we can calculate a retardation factor for the dye. The lowest detectable dye concentrations encountered in some studies are 0.1 g l 21 (Ewing and Horton, 1999) and 0.2 g l 21 (Aeby et al, 1997). Forrer et al (2000) reported a lower limit of 0.04 g l 21 soil, however, they did not report the water content.…”
Section: Comparison Of Bromide and Dye Coverage In One Fingermentioning
confidence: 88%
“…We further developed the processing and classification of dye patterns form vertical and horizontal soil sections based on earlier studies (Aeby et al, 1997;Forrer et al, 2000). The fast and objective method allows clear delineation of stained and unstained areas and classification of stained areas into concentration categories.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the work of Aeby et al (1997), we developed and applied a robust semi-supervised classification technique to discriminate stained from unstained areas and to classify the tracer concentration into three categories. Image segmentation, where each pixel is assigned to a particular object or region, was chosen as classification technique (Castleman, 1996).…”
Section: Image Processing and Classificationmentioning
confidence: 99%
“…One of the most popular staining dyes used in vadose zone hydrology is Brilliant Blue FCF. Evaluations of Brilliant Blue (BB) dye concentrations in a natural soil profile enabled quantification of the subsurface flux (Aeby et al, 1997;Forrer et al, 2000), in addition to more traditional assessments of stained and unstained portions of soil profiles. In the past decade fluorescent dyes have been proposed as staining tracers while methods for quantifying tracer concentrations were developed concurrently (Aeby et al, 2001;Duwig et al, 2008;Vanderborght et al, 2002).…”
Section: Introductionmentioning
confidence: 99%